Cost Shares and Factor-Cost Ratios in Owner-Built Incremental Housing in Dar Es Salaam, Tanzania - Sanga, Samwel Alananga; Lucian, Charles (Penerbit Universiti Sains Malaysia, 2016)
The adoption of incremental owner-built techniques in housing construction relies on the associated lower cost compared to developer-built approaches. The mechanism that lowers cost is however, not obvious. This study is based on survey data that were collected using questionnaires which were distributed to 200 respondents in Dar es Salaam, Tanzania with response rate of 22.5%. The analysis results, based on descriptive statistics and regression analysis indicate that an incremental house-builder targeting an additional bedroom incrementally spends 28% lower annual construction cost and each additional square meter built, is associated with 0.4% lower cost. However, such lower cost comes at a 5%–10% longer completion time. These observations suggest that spreading costs over time reduces construction cost through multiple cost-saving channels opened up by time itself and factor intensity. The intensity of incremental housing construction favours increasing expenditure on labour than capital yielding a 5% reduction in annual cost but the greatest cost reduction benefit of up to 26% is realised through increasing expenditure on "capital" with fixed spending on materials during construction.